HUBUNGAN ANTARA MOTIVASI BELAJAR DENGAN KETERAMPILAN ARGUMENTASI PADA MAHASISWA BIOLOGI - Astuti Muh Amin; Romi Adiansyah; Noor Hujjatusnaini (Jurnal Biotek, 2021)
Learning motivation serves as a catalyst and a driver of student behavior toward academic success. Studies on the relationship between motivation and argumentation skills acquisition in biology education are relatively uncommon. This study evaluated the correlation between biology students’ learning motivation and their argumentation skills. This study employed a correlational design. The population for this study was composed entirely of students from the Biology Departments at IAIN Ternate and STKIP Kie Raha, both located in North Maluku, Indonesia. This study involved 110 students from IAIN Ternate and STKIP Kie Raha. Those selected by random sampling. The instruments used in this study were proven to be valid and reliable for assessing students’ learning motivation and argumentation skills. The data evaluated using regression analysis at a 0.05 level of significance. There was no correlation between students’ motivation and argumentation skills in RQA, ADI, ADI-Integrated RQA, or conventional classrooms. This finding might be influenced by several factors. First, the students are unfamiliar with the model. Hence, they require additional time to adjust to the learning phases. The next factor is that students lack the necessary capacity to integrate prior learning experiences into their understanding of acquired concepts. Another factor is the lack of learning facilities and infrastructure. Nonetheless, this study serves as a springboard for future research on similar themes to improve the quality of college instruction and the graduate